Sustaining effective individualized behavior support: Barriers and enablers. Issue 1 (2nd January 2019) - Strickland-Cohen, Monica Kathleen; Pinkelman, Sarah E.; Jimerson, Jo Beth; Berg, Tricia A.; Pinkney, Christopher J.; McIntosh, Kent
ABSTRACT: Function-based support is a widely researched and highly effective form of intervention for students with persistent problem behavior. However, individualized behavior support practices for students continue to be implemented inconsistently in school settings, and educators often use valuable resources adopting interventions that are not likely to be successfully implemented or sustained over time. This article presents findings from a follow-up study of school personnel trained to design and implement function-based behavior support for students with challenging behavior. The purpose of the study was to determine (a) the extent to which participants continued to use the skills learned during their training after the removal of all formal research supports and (b) the perceived barriers and enabling factors personnel encountered when continuing to provide function-based student support.